Online Headlines in Croatian and Lithuanian News Media - Podboj, Martina; Vitkūnė-Bajorinienė, Aistė (Respectus Philologicus, 2025)
The headline is a salient element of the news story, whose aim is to summarise the story and attract attention to its full text. The internet and online news dissemination and consumption have strongly transformed journalistic discourse, including headlines, which have become longer, significantly more complex, and multifaceted in their aim to attract readers’ attention. This paper presents the results of a qualitative comparative study of online headlines published on Croatian and Lithuanian media outlets from a discourse-analytic perspective. The data was collected from four top-read online news outlets (jutarnji.hr, index.hr, lrytas.lt, delfi.lt) and qualitatively analysed bearing in mind linguistic and visual strategies used to frame the news story and attract readers’ attention. The analysis showed that similar clickbait and narrative strategies are consistently aggregated across semiotic modes in all four news outlets in both countries. Apart from minor context-specific distinctions, no substantial differences were noticed in the overall discourse of headlines in the Croatian and Lithuanian observed media outlets.